Effects of imidacloprid on the ecology of sub-tropical freshwater microcosms. (May 2018) - Sumon, Kizar Ahmed; Ritika, Afifat Khanam; Peeters, Edwin T.H.M.; Rashid, Harunur; Bosma, Roel H.; Rahman, Md. Shahidur; Fatema, Mst. Kaniz; Van den Brink, Paul J.
Abstract: The neonicotinoid insecticide imidacloprid is used in Bangladesh for a variety of crop protection purposes. Imidacloprid may contaminate aquatic ecosystems via spray drift, surface runoff and ground water leaching. The present study aimed at assessing the fate and effects of imidacloprid on structural (phytoplankton, zooplankton, macroinvertebrates and periphyton) and functional (organic matter decomposition) endpoints of freshwater, sub-tropical ecosystems in Bangladesh. Imidacloprid was applied weekly to 16 freshwater microcosms (PVC tanks containing 400 L de-chlorinated tap water) at nominal concentrations of 0, 30, 300, 3000 ng/L over a period of 4 weeks. Results indicated that imidacloprid concentrations from the microcosm water column declined rapidly. Univariate and multivariate analysis showed significant effects of imidacloprid on the zooplankton and macroinvertebrate community, some individual phytoplankton taxa, and water quality variables (i.e. DO, alkalinity, ammonia and nitrate), with Cloeon sp., Diaptomus sp. and Keratella sp. being the most affected species, i.e. showing lower abundance values in all treatments compared to the control. The observed high sensitivity of Cloeon sp. and Diaptomus sp. was confirmed by the results of single species tests. No significant effects were observed on the species composition of the phytoplankton, periphyton biomass and organic matter decomposition for any of the sampling days. Our study indicates that (sub-)tropical aquatic ecosystems can be much more sensitive to imidacloprid compared to temperate ones. Graphical abstract: Image 1 Highlights: We are the first to assess effects of imidacloprid on freshwater microcosms in Bangladesh. Invertebrates were much more sensitive to imidacloprid than any other organisms. Multiple applications of 30 ng/L imidacloprid showed significant ecological effects. Sub-tropical species proved to be much more sensitive to imidacloprid than temperate ones.